2019
DOI: 10.1021/acs.orglett.9b01046
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Formation of RSCl/ArSeCl and Their Application to the Synthesis of 4-Chalcogenylisocumarins/Pyrones from o-(1-Alkynyl)benzoates and (Z)-2-Alken-4-ynoates

Abstract: The reaction of diorganyl disulfides or diselenides with PhICl2 in acetonitrile was found for the first time to lead to the in situ formation of organosulfenyl chloride or selenenyl chloride, which enables the regioselective intramolecular chalcogenylacyloxylation of alkynes resulting in the formation of 4-chalcogenylisocumarins/pyrones in good to excellent yields under metal-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…Among them, the intramolecular cyclization of the 2‐alkynylbenzoates or 2‐alkynylbenzic acids has emerged as an effective and powerful process for the construction of isochromenone framework , . Meanwhile, diverse substituents can be introduced at the 4‐position of the isochromenones , . Although C sp 2 –S bond formation had been widely reported, the preparation of 4‐sulfenylisochromenones has been less explored due to the limitation on their synthetic strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the intramolecular cyclization of the 2‐alkynylbenzoates or 2‐alkynylbenzic acids has emerged as an effective and powerful process for the construction of isochromenone framework , . Meanwhile, diverse substituents can be introduced at the 4‐position of the isochromenones , . Although C sp 2 –S bond formation had been widely reported, the preparation of 4‐sulfenylisochromenones has been less explored due to the limitation on their synthetic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Ding and co‐workers found that the incorporation of the (trifluoromethyl)thio group into the isochromenone scaffold can be realized through a Lewis acid‐induced electrophilic cyclization of 2‐alkynylbenzoates with trifluoromethanesulfanylamide (Scheme c). Most recently, our own group found that 4‐sulfenylisocoumarins could be readily achieved from the reaction of 2‐alkynylbenzoates with organosulfenyl chloride (RSCl), generated in situ from diorganyl disulfides with PhICl 2 in acetonitrile (Scheme d) . Although these 4‐sulfenylisochromenones with different substitution patterns have been successfully synthesized, there are few reports on the construction of isochromenone skeleton bearing the biological interesting methylthio substituent in its 4‐position , …”
Section: Introductionmentioning
confidence: 99%
“…[8] Inspired by this work, we are interested to understand whether this one-pot strategy could be applied in the introduction of thio and selenyl functional groups to enaminone and its analogues. [8] Inspired by this work, we are interested to understand whether this one-pot strategy could be applied in the introduction of thio and selenyl functional groups to enaminone and its analogues.…”
Section: Communications Ascwiley-vchdementioning
confidence: 99%
“…However, further decrease in the oxidant amount led to a slight drop in the reaction yield (entry 4). Afterward, a series of solvents including DMF, DCM, methanol, THF, and CF 3 CH 2 OH were tested and only DMF provided superior result (entries [5][6][7][8][9]. Conducting the reaction under an ice-bath rather than at room temperature gave similar results (entry 10).…”
mentioning
confidence: 99%
See 1 more Smart Citation